Potential Medications or Compounds Acting on Toll-like Receptors in Cerebral Ischemia - Li, Man (Curr Neuropharmacol, 2018)
BACKGROUND: Toll-like receptors play an integral role in the process of inflammatory response after ischemic in-jury. The therapeutic potential acting on TLRs is worth of evaluations. The aim of this review was to introduce readers some potential medications or compounds which could alleviate the ischemic damage via TLRs. METHODS: Research articles online on TLRs were reviewed. Categorizations were listed according to the follows, methods acting on TLRs directly, modulations of MyD88 or TRIF signaling pathway, and the ischemic tolerance induced by the pre-conditioning or postconditioning with TLR ligands or minor cerebral ischemia via acting on TLRs. RESULTS: There are only a few studies concerning on direct effects. Anti-TLR4 or anti-TLR2 therapies may serve as promis-ing strategies in acute events. Approaches targeting on inhibiting NF-κB signaling pathway and enhancing interferon regu-latory factor dependent signaling have attracted great interests. Not only drugs but compounds extracted from traditional Chinese medicine have been used to identify their neuroprotective effects against cerebral ischemia. In addition, many re-searchers have reported the positive therapeutic effects of preconditioning with agonists of TLR2, 3, 4, 7 and 9. Several trails have also explored the potential of postconditioning, which provide a new idea in ischemic treatments. Considering all the evidence above, many drugs and new compounds may have great potential to reduce ischemic insults. CONCLUSION: This review will focus on promising therapies which exerting neuroprotective effects against ischemic injury by acting on TLRs.